2020
DOI: 10.1016/j.idairyj.2020.104729
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad and the aged: Predicting sensory quality of anhydrous milk fat by PTR/SRI-Tof-MS analysis and data mining

Abstract: Due to its versatility, anhydrous milk fat (AMF) has become more popular as a food industry ingredient, but its quality control remains a critical challenge. A direct injection mass spectrometry technique was applied to predict sensory quality of AMF. Volatilome analysis through proton transfer reaction mass spectrometry (PTR-MS) was used to classify 39 industrial samples of AMF according to industrial sensory evaluation and to accelerated ageing. A selective reagent ion system was used to evaluate the suitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For OVOCs, the proton affinities (PAs) are much higher compared with those of unsaturated hydrocarbons. Thus, the proton transfer reaction (PTR) based on the H 3 O + (PA = 691 kJ/mol) reactant ion is suitable for efficient ionization of OVOCs. Shu et al , reported a VUV-excited and CH 2 Cl 2 /H 2 O-amplified ionization process by introducing a gas mixture of CH 2 Cl 2 /H 2 O into the VUV ion source to generate large amounts of H 3 O + ions. Then, the PTR between the H 3 O + reactant ions and analyte molecules occurred to produce analyte ions [MH] + and [MH] + ·H 2 O with the ion source pressure in the range of 500–1300 Pa.…”
mentioning
confidence: 99%
“…For OVOCs, the proton affinities (PAs) are much higher compared with those of unsaturated hydrocarbons. Thus, the proton transfer reaction (PTR) based on the H 3 O + (PA = 691 kJ/mol) reactant ion is suitable for efficient ionization of OVOCs. Shu et al , reported a VUV-excited and CH 2 Cl 2 /H 2 O-amplified ionization process by introducing a gas mixture of CH 2 Cl 2 /H 2 O into the VUV ion source to generate large amounts of H 3 O + ions. Then, the PTR between the H 3 O + reactant ions and analyte molecules occurred to produce analyte ions [MH] + and [MH] + ·H 2 O with the ion source pressure in the range of 500–1300 Pa.…”
mentioning
confidence: 99%
“…A mass peaks selection procedure (Pedrotti et al, 2020) was applied to extract relevant information and reduce noise signal associated to PTR-ToF-MS measurements. This procedure allowed to select 179 peaks (first experiment), 212 peaks (second experiment), 120, 104 and 105 peaks (third experiments H 3 O + , O 2 + and NO + ) for further statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…freshness, adulteration, quality classification) (for an overview see: Ellis & Mayhew, 2014). Some of the most recent PTR-MS applications examples are in saffron (Nenadis, Heenan, Tsimidou, & Van Ruth, 2016) and anhydrous milk fat (Pedrotti et al, 2018(Pedrotti et al, , 2020 quality control, for evaluating shelf life of poultry meat (Wojnowski et al, 2018) and lactose free milk (Bottiroli et al, 2020) and for botanical and geographical origins characterization of both cocoa (Acierno, Yener, Alewijn, Biasioli, & Van Ruth, 2016) and coffee beans (Yener et al, 2014(Yener et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Along with applications during shelf life, PTR-MS has been used to predict the quality class of different foods, including spices [101] , chocolate [102] , milk [103] , and AMF [104] . In all the cases, PTR-MS volatile fingerprints were used to predict the quality classes obtained from sensory and standard quality measurements.…”
Section: Quality Controlmentioning
confidence: 99%